The relationship between visit-to-visit variability in blood pressure and incidence of metabolic syndrome: a general population-based cohort study in Korea - Hyung Tak Lee; June Namgung; Young-Hyo Lim; Hwan-Cheol Park; Jin-Kyu Park; Jinho Shin (BMC, 2019)
Abstract Background Previous studies demonstrated that visit-to-visit variability of blood pressure (BP) has significant relationship with cardiovascular disease. Visit-to-visit variability in BP might have prognostic value for cardiovascular disease. The aim of this study is to evaluate the effect of visit-to-visit variability in BP on development of metabolic syndrome in general population without cardiovascular disease, diabetes mellitus, metabolic syndrome, and BP medication. Method We used data from the Korean Genome Epidemiology Study conducted by the Korean Centers for Disease Control and Prevention. All cohorts who were followed first 3 periods formed the basis of the study sample, which consisted of 7195 people. Of these samples, 3431 subjects who had cardiovascular disease, diabetes mellitus, or metabolic syndrome were excluded, and 312 subjects who were using antihypertensive medication in first 3 periods were excluded. Our final study sample consisted of 3452 cohorts. Results The mean age was 53.5 (8.25) years. The proportion of male was 50.2%. Average follow-up duration was 5.91 (0.17) years. In generalized estimating equation, the development of metabolic syndrome was associated with mean systolic BP (SBP) (Odd ratio (OR) 1.042, 95% confidence interval (CI) 1.035-1.048, p < 0.001), mean diastolic BP (DBP) (OR 1.058, 95% CI 1.049-1.069, p < 0.001), standard deviation (SD) of SBP (OR 1.036, 95% CI 1.017-1.055, p < 0.001), SD of DBP (OR 1.053, 95% CI 1.027-1.080, p < 0.001), and coefficient of variation (CV) of DBP (OR 1.025, 95% CI 1.005-1.046, p = 0.016) after adjusted for age, sex, and metabolic syndrome component. When mean SBP, mean DBP, SBP variability, and DBP variability were entered all together in the analysis model, SD of DBP (OR 1.033, 95% CI 1.003-1.063, p = 0.030) and CV of DBP (OR 1.027, 95% CI 1.004-1.051, p = 0.020) were significantly associated with the development of metabolic syndrome. Conclusion In general population without cardiovascular disease, diabetes mellitus, metabolic syndrome, and BP medication, SD of DBP and CV of DBP was associated with the development of metabolic syndrome. Visit-to-visit variability in DBP might be helpful for the prediction of future metabolic syndrome development.